Upper Turonian-lower Campanian planktonic foraminifera from southern mid-high latitudes (Exmouth Plateau, NW Australia): Biostratigraphy and taxonomic notes - M.R. Petrizzo (Cretaceous Research, 2000)
A planktonic foraminiferal zonal scheme is presented for subdivision of the Upper Cretaceous pelagic carbonate sequence from southern mid-high latitudes. Definition of the zones is based on first and last occurrences of planktonic foraminifera from Ocean Drilling Program Holes 762C and 763B (Leg 122; Exmouth Plateau, south Indian Ocean). During the Late Cretaceous the studied holes were located close to 50°S and for the first time a complete sedimentary record for the mid-high latitudes was obtained. A detailed biostratigraphic analysis has allowed recognition of two new zones (Falsotruncana maslakovae Zone and Marginotruncana marianosi Zone) for the interval extending from the last occurrence of Helvetoglobotruncana helvetica to the first occurrence of Dicarinella asymetrica (upper Turonian-lower Santonian). From this study it is apparent that some low latitude (Globotruncana ventricosa, Hedbergella flandrini, Marginotruncana marianosi) and high latitude (Globigerinelloides impensus and Hedbergella sliteri) marker taxa display a vertical distribution at mid-high latitudes which is different from that known from low latitudes; moreover, one species (Heterohelix papula), overlooked at low latitudes, exhibits a restricted range that seems to be useful for chrono-biostratigraphic correlations: its appearance is suggested to coincide with the Coniacian/Santonian boundary. The proposed biozonation, which is integrated with calcareous nannofossil and magnetostratigraphic data available for the sections studied, is compared with both the low-latitude standard zonation and the planktonic foraminiferal zonal scheme for the circum-Antarctic region, in order to define a bio-chronostratigraphic scale that is useful for mid-high latitudes of the southern oceans.